Latent tuberculosis infection in patients with chronic plaque psoriasis: evidence from the Italian Psocare Registry. (1st June 2015) - Gisondi, P.; Cazzaniga, S.; Chimenti, S.; Maccarone, M.; Picardo, M.; Girolomoni, G.; Naldi, L.; ,; Griseta, V.; Miracapillo, A.; Azzini, M.; Mocci, L.; et al.
Summary: Background: The nationwide prevalence of latent tuberculosis infection (LTBI) in Italian patients with psoriasis has never been investigated. Objectives: To estimate the nationwide prevalence of LTBI in Italian patients with psoriasis who are candidates for systemic treatment. Methods: Data were obtained from the Psocare Registry on those patients ( n = 4946) with age > 18 years, systemic treatment at entry specified and tuberculin skin test (TST) performed according to the Mantoux method. LTBI diagnosis was based on a positive TST result in the absence of any clinical, radiological or microbiological evidence of active tuberculosis. Results: Latent tuberculosis infection was diagnosed in 8·3% of patients with psoriasis (409 of 4946). The prevalence of LTBI was lower in patients on biologics than in those on conventional systemic treatments, ranging from 4·3% (19 of 444) of patients on adalimumab to 31% (eight of 26) of those on psoralen–ultraviolet A ( P < 0·05). Independent factors associated with LTBI were male sex [odds ratio (OR) 1·30, 95% confidence interval (CI) 1·04–1·62; P = 0·02], age over 55 years (OR 2·93, 95% CI 2·18–3·93; P < 0·001) and being entered into a conventional treatment (OR 3·83, 95% CI 3·10–4·74; P < 0·001). Positive history of tuberculosis was seen in 1% of patients ( n = 49). Conclusions: The nationwide prevalence of LTBI in Italian patients with psoriasis candidate to systemic treatment is high, and screening is recommended prior to biological treatment.